The family Rhabdoviridae: mono- and bipartite negative-sense RNA viruses with diverse genome organization and common evolutionary origins - Dietzgen, Ralf G.; Kondo, Hideki; Goodin, Michael M.; Kurath, Gael; Vasilakis, Nikos (Virus research, 2017)
[Display omitted] •Family Rhabdoviridae is comprised of thirteen genera.•Rhabdoviruses are mostly enveloped and infect ecologically diverse hosts.•Rhabdovirus negative-sense RNA genome has five canonical structural protein genes.•Rhabdovirus genomes may contain additional ORFs encoding putative accessory proteins.•Diverse genome structure may guide taxonomic resolution at genus and species levels. The family Rhabdoviridae consists of mostly enveloped, bullet-shaped or bacilliform viruses with a negative-sense, single-stranded RNA genome that infect vertebrates, invertebrates or plants. This ecological diversity is reflected by the diversity and complexity of their genomes. Five canonical structural protein genes are conserved in all rhabdoviruses, but may be overprinted, overlapped or interspersed with several novel and diverse accessory genes. This review gives an overview of the characteristics and diversity of rhabdoviruses, their taxonomic classification, replication mechanism, properties of classical rhabdoviruses such as rabies virus and rhabdoviruses with complex genomes, rhabdoviruses infecting aquatic species, and plant rhabdoviruses with both mono- and bipartite genomes.